Reengineering of educational material: a systematic approach. (16th September 2005) - Pankratius, Victor; Vossen, Gottfried
In electronic learning, keeping learning material up-to-date is a recurring problem. In the past, this has mostly been done manually, with a frequent consequence that material becomes outdated since manual updates are neither systematic nor applied often enough. In this paper, we take a software engineering perspective on the problem of updating learning material for electronic platforms, and show how reengineering can help in this context. Specifically, we present a reference model for an e-learning reengineering process, and cast this model into the architecture of a component and configuration management system. Finally, we indicate how the approach can be exploited by showing an example, and outlining a global reuse strategy for educational material using software product lines.